Equitable access to quality injury care; Equi-Injury project protocol for prioritizing interventions in four low- or middle-income countries: a mixed method study - Equi-Injury Group (BMC, 2024)
Abstract Background Equitable access to quality care after injury is an essential step for improved health outcomes in low- and middle-income countries (LMICs). We introduce the Equi-Injury project, in which we will use integrated frameworks to understand how to improve equitable access to quality care after injury in four LMICs: Ghana, Pakistan, Rwanda and South Africa. Methods This project has 5 work packages (WPs) as well as essential cross-cutting pillars of community engagement, capacity building and cross-country learning. In WP1, we will identify needs, barriers, and facilitators to impactful stakeholder engagement in developing and prioritising policy solutions. In WP2, we will collect data on patient care and outcomes after injuries. In WP3, we will develop an injury pathway model to understand which elements in the pathway of injury response, care and treatment have the biggest impact on health and economic outcomes. In WP4, we will work with stakeholders to gain consensus on solutions to address identified issues; these solutions will be implemented and tested in future research. In WP5, in order to ascertain where learning is transferable across contexts, we will identify which outcomes are shared across countries. The study has received approval from ethical review boards (ERBs) of all partner countries in South Africa, Rwanda, Ghana, Pakistan and the University of Birmingham. Discussion This health system evaluation project aims to provide a deeper understanding of injury care and develop evidence-based interventions within and across partner countries in four diverse LMICs. Strong partnership with multiple stakeholders will facilitate utilisation of the results for the co-development of sustainable interventions.